Antenna Analytical Representation by a Two-Port Network - Peter L. Tokarsky (International Journal of Antennas and Propagation)
System analysis is a powerful tool for researching modern wireless systems. This includes breaking such systems into parts that make them up and studying how these parts work together. All these parts can be represented as “black boxes” in the form of two-port or multiport networks with the common system of parameters. Antenna is an integral part of any wireless system, so it should be also represented as a two-port network. In this paper, an analytical model of an arbitrary single antenna in the form of a two-port network, whose electrical and noise parameters are described in terms of scattering matrices, is obtained. The initial data for creating the model are the antenna fundamental parameters, viz., the input reflection coefficient and the radiation efficiency. Applications of this model for antenna analysis operating in the transmitting, receiving, and scattering modes are demonstrated. A numerical example using the antenna scattering matrix for computer simulation of a wireless connection is given.